Rheology and thermal conductivity of calcium grease containing multi-walled carbon nanotube. Issue 4 (2nd April 2016) - Kamel, Bahaa M.; Mohamed, Alaa; El Sherbiny, M.; Abed, K. A.
ABSTRACT: Recently, nanofluids attract considerable interest for enhanced rheological behavior and thermal performance. The aim of this research is to study the influence of additives Multi-Walled Carbon Nanotubes (MWCNTs) on the rheological behavior and its structure, thermal conductivity, and the influence of shear thinning rate on oil separation at different temperatures for calcium grease. Various concentrations of MWCNTs (0.5, 1, 2, 3, and 4%) have been added to the grease to obtain the best percentages that improve the properties of nanofluid. The microstructure of MWCNTs and nanofluid were examined by X-ray diffraction (XRD), Transmission Electron Microscope (TEM), and Scanning Electron Microscope (SEM). These experimental investigations were evaluated with a Brookfield programmable Rheometer DV-III ULTRA. The results indicated that the optimum concentration of MWCNTs was 3%, and the dropping point increasing about 11%. The rheological behaviors of the nanofluids show that the grease with various concentrations of MWCNTs demonstrates non Newtonian behaviors and the results indicated that the shear stress, apparent viscosity and thermal conductivity increase with the increase of volume concentration of MWCNTs to 65%, 52%, and% 56, respectively.